ANALISIS KEPUASAN KONSUMEN DI CAFÉ ONE REFINERY KOTA PEKANBARU - Utomo Ramadhan Ivan; Wasnury Rendra; Noviasari Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research has the aim of determine the consumer satisfaction index andstrategies to improve the service quality of Café One Refinery Pekanbaru City.The population in this study includes all visitors to Café One Refinery PekanbaruCity, totaling 100 people. The sample was determined using purposive samplingmethod. In this study, the sample studied used a questionnaire. Hypothesis testingin this study uses CSI (Customers Satisfaction Index) analysis and IPA(Importance Performance Analysis) analysis with the help of the SPSS program.The results showed that the overall consumer satisfaction index given by CaféOne Refinery Pekanbaru City was